Stanko Vraz in nacionalizem Od narobe Katona do narobe Prešerna - Jež, Andraž (Studia litteraria, 2016)
For a century and half, the life and work of the Slovenian-Croatian poet Stanko Vraz (1810-1851) has aroused mutually irreconcilable interpretations in Slovenian literary history and Slovenian public. These ambiguous receptions usually ranged between praising Vraz as a visionary Styrian poet and dismissing him as a "national renegade." On one side, the Slovenian reception of Vraz centered on his decision to abandon writing in Slovenian and to embrace Shtokavian Croatian. On the other side, Vraz was an internationally acclaimed Illyrian poet and romantic Pan-Slav that almost single-handedly kindled the flame for the Slovenian national rebirth in pre-March Lower Styria. Moreover, Slovenian literary historiography adds to his ambiguous status by treating him as a unique and often tragic figure. Despite his mythicized role, Stanko Vraz in nacionalizem (Stanko Vraz and Nationalism) depicts Vraz from another angle-as a symptom of these processes rather than as their main protagonist. To achieve this task, the book offers a new contextualization of Vraz's practice and provides a new look at the Slovenian posthumous reception of the poet.